2022
DOI: 10.31219/osf.io/g63sh
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Unique Role for Social Connection in the COVID-19 Pandemic; A Qualitative Analysis of Parenting Forums

Abstract: The COVID-19 pandemic has disproportionately impacted parents, though few studies have explored stressors from parents’ perspectives. This study aimed to understand parental stressors and how parents seek information about mental health, parenting stress, and social support online during the COVID-19 pandemic. A total of 337 threads focusing on parenting questions and discussions on two popular online forums, Baby Centre Canada and Canadian Parents What to Expect, were analyzed using a qualitative framework an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…These requests aligned with our knowledge synthesis work highlighting the importance of therapist contact (vs. only didactic materials) to symptom improvement in digital programs (30). Similarly, our previous qualitative research on parenting forums (1,000 posts) during the pandemic highlighted requests for strategies to support family mental health and to feel less isolated (31).…”
Section: Building Emotional Awareness and Mental Health Program Devel...supporting
confidence: 70%
“…These requests aligned with our knowledge synthesis work highlighting the importance of therapist contact (vs. only didactic materials) to symptom improvement in digital programs (30). Similarly, our previous qualitative research on parenting forums (1,000 posts) during the pandemic highlighted requests for strategies to support family mental health and to feel less isolated (31).…”
Section: Building Emotional Awareness and Mental Health Program Devel...supporting
confidence: 70%
“…The forum was also noted to be beneficial, as it provided an opportunity to connect with other mothers in the program, share stories, talk about program content, and seek advice. Other research on parenting forums among mothers has found similar conversation topics (Pierce et al, 2022) with similar beneficial impacts. Online forums are shown to be an effective source of support for mothers across various populations (Baum, 2004;Reinke & Solheim, 2015;Wagg et al, 2019) providing a valuable and empowering community, and an informal knowledge base for the challenges of parenting (Brady & Guerin, 2010;Doty & Dworkin, 2014).…”
Section: Discussionmentioning
confidence: 70%